2015
DOI: 10.1111/isqu.12201
|View full text |Cite
|
Sign up to set email alerts
|

Believing This and Alieving That: Theorizing Affect and Intuitions in International Politics

Abstract: Rationalist models of decision making typically follow the general form of desire + belief = action. But determining an actor's beliefs and desires often proves challenging. One set of theories turns to psychology—and in particular emotions—to uncover how emotions help to shape and strengthen beliefs. Some of this work establishes a fit between emotions and the rationalist paradigm. It holds that emotions account for more than irrational behaviors; they also serve as a source of rational belief. Feeling, it cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 76 publications
3
16
0
1
Order By: Relevance
“…19 O nosso problema não é o de discutir as várias lógicas de ação: lógica argumentativa; lógica consequencial; lógica apropriada; lógica dos hábitos; lógica das práticas; lógica emocional; lógica intuitiva, etc. (March e Olsen, 1998;Pouliot, 2008;Hutchison e Bleiker, 2014;Holmes, 2015). O nosso argumento é que os decisores não decidem de uma forma linear e mecanicamente racional.…”
Section: A Importância Das Ideias: Uma Visão So Cioló Gicaunclassified
“…19 O nosso problema não é o de discutir as várias lógicas de ação: lógica argumentativa; lógica consequencial; lógica apropriada; lógica dos hábitos; lógica das práticas; lógica emocional; lógica intuitiva, etc. (March e Olsen, 1998;Pouliot, 2008;Hutchison e Bleiker, 2014;Holmes, 2015). O nosso argumento é que os decisores não decidem de uma forma linear e mecanicamente racional.…”
Section: A Importância Das Ideias: Uma Visão So Cioló Gicaunclassified
“…Marcus Holmes (2013) has recently applied such a dual axis in a compelling manner. They distinguish, for instance, between cognitive and affective, as well as between latent and emergent approaches.…”
Section: Early Attempts To Address the Curious Absence Of Theorizing mentioning
confidence: 99%
“…Rather than forming a pre-existing background, emotions here are seen as 'emergent properties' of an interactive body-mind system (Coan 2010, 278), which itself has been constituted over time through socially and cultural conditioned forms of perception and experience (see also Holmes 2013). Latent models assume emotions are always already present.…”
Section: Early Attempts To Address the Curious Absence Of Theorizing mentioning
confidence: 99%
See 1 more Smart Citation
“…Yarhi‐Milo's () Knowing the Adversary: Leaders, Intelligence, and Assessment of Intentions in International Relations demonstrates that policymakers often make decisions about the intentions of states not just by looking at structural factors, but instead by relying on preexisting beliefs and personal impressions. I (Holmes , ) have similarly suggested that there are neuroscientific reasons for diplomats to trust the intuitions and beliefs that they derive of the intentions of others through face‐to‐face diplomacy. Substantively, this renaissance of diplomacy studies has been applied to a wide range of subjects, from current EU politics (Adler‐Nissen ), to the formation of forum talk in the Concert of Europe (Mitzen ), to resolving hostilities between enemies (Wheeler ), to the day‐to‐day practices of diplomats (Pouliot ; Neumann ; Bjola and Holmes ; Sandre ), and to the existence of discrete diplomatic cultures and traditions (Sharp ; Constantinou ).…”
mentioning
confidence: 99%